Development of a 3-Tier Effective Teaching Model for Teachers towards MOOC in Higher Education in Pakistan - Ali Shah, Masoomi Hifazat; Keerio, Imran Khan; Shah, Asadullah (GCLT (Global Center for Legal Thought), Islamabad, 2023)
Introduction - MOOC is the foundation of a distance learning platform in reshaping education by adopting information technology infrastructure that aims to enhance quality education and provide opportunities for learners to acquire knowledge and skills at their doorstep. MOOCs can be accessed and delivered by teachers who transfer their expertise to learners who can acquire the ability of technical skills, and critical thinking through digital transformation. The MOOC teachers lack digital skills and deliver inadequate instruction that leaps worthless MOOCs from learners' perspective. This research has utilized the (UTAUT) Unified Theory of Acceptance and Use of Technology model and identified the research hypotheses that influence teachers' behavior intention towards the use of MOOCs in higher education. This research has used a quantitative approach and designed a survey questionnaire for data collection to examine the effect of independent and dependent variables. The targeted survey audience had only teachers who are teaching in MOOC. SPSS and PLS-SEM 3 statistical tools were used for data analysis and interpretation. The research outline identifies the impact of a 3-tier effective teaching model for teachers towards MOOC and suggests 12 hypothesis that extends amended UTAUT with digital literacy, digital pedagogy, and attitude towards MOOC, denoted as a 3-tier effective teaching model as factors. The pretesting conclusion in the context indicates that the data collection instrument is sufficient to develop for future research since it has the coefficient alpha (α) significant values are DL(0.830), DP(0.790), ATT(0.912), PE(0.909), EE(0.891), SI(0.827), FC(0.706), BI(0.822), USE(0.824) below the specified level. This study reveals the strong status of teachers teaching towards MOOC and also contributes to the pieces of literature by adopting the UTAUT model for IT/IS acceptance and use.